Effect of Αlfa-Tocopherol on Pain and Inflammation of Rats - Juaira, Tasneema; Begum, Noorzahan; Yusuf, Md Abdullah; Patwary, Mohammad Asaduzzaman (Journal of Current and Advance Medical Research, 2018)
Background: Alfa-tocopherol (αT) is a naturally occurring lipid soluble anti-oxidant that protects our body from oxidative process. Objective: The purpose of the present study was to assess the effects of α-tocopherol on pain and inflammation in rats. Methodology: This prospective experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka, Bangladesh from January 2013 to December 2013. Ten (10) male Long Evans rats, weighing 180 to 250 grams, were collected from Bangladesh Institute of Research and Rehabilitation for Diabetic Endocrine and Metabolic Disorders (BIRDEM), Shahbag, Dhaka for this purpose. On the basis of vitamin, all the rats were divided into two (02) groups (5 rats in each group). Group A received normal saline and group B received α-tocopherol. All the groups received single dose and equal volume through intraperitoneal route. Just one hour after administrations, 5 rats of each group were subjected to formalin test followed by formalin induced paw edema test. Results: In early, inter and late phases, the frequencies of jerking was significantly lower in group B than that of group A. In the early and late phases of formalin test duration of flexing and licking was significantly (p<0.05) lower in group B than that of group. In this study, mean±SE of paw edema volume in group A (0.28 ± 0.02 ml) was higher than that of group B (0.20 ± 0.03) but the difference was not statistically significant (p=0.070). Supplementation with single loading dose of α-tocopherol significantly (p<0.05) lowered the variables for nociceptive pain, central analgesic activity and inflammatory pain in comparison to normal saline treated group (control). Inflammations were also non-significantly reduced than those of control rats. Conclusion: From this study it may be concluded that, single loading dose of α-tocopherol have analgesic and anti-inflammatory effect. Journal of Current and Advance Medical Research 2018;5(1):15-18